Short - Sloan, Holly Goldberg, 1958- (Puffin Books, 2018)
When Julia gets cast as a munchkin in a local production of "The Wizard of Oz," she has even more reason to hate her short stature. But as she gets to know the show's enthusiastic director and eccentric cast, Julia's summer might become worthwhile after all.